A new method to gently place biopsy needles or treatment electrodes into tissues with high target precision. Issue 5 (May 2016) - Wiksell, Hans; Löfgren, Lars; Schässburger, Kai-Uwe; Leifland, Karin; Thorneman, Karin; Auer, Gert
Highlights: Unique acceleration-pulsed imaging guided insertion of treatment electrode. Servo-controlled pulse action optimizes insertion. Synchronized anti-seeding system reduces tumor cell dissemination. Abstract: We present a new core needle biopsy and treatment electrode precision placement technique which, regardless of needle size, target lesion hardness and elasticity, makes it possible to precisely place an image guided device inside the abnormal tissue. Once inside the abnormal lesion, multiple tissue samples can be collected using a dedicated trocar and collecting system. Our unique "Fourier" driver substitutes the commonly used spring-loaded device or complements the jerky insertion technique used by experienced interventional physicians. It enables the physician to precisely and with extreme tactility maneuver even large diameter core needles or treatment-electrodes into the lesion using only a diminutive external force. This is achieved by applying supporting servo-controlled mechanical high-acceleration micro-pulses, proportional to the average vector directed by the physician. The Fourier-needle or Fourier-electrode stands completely non-moving when the system automatically goes into full idling. This means that the angle of attack successively and arbitrary can be aligned to hit the target, becoming successively symmetrically inserted into even small tumors to be treated as well as exactly hit any point outlined by real time ultrasound guiding. This kind of biopsy needle or treatment electrode placement results in a uniquely accurate and less traumatic procedure. Due to the risk of disseminating viable tumor cells the precision placement device can be combined with a computer controlled anti-seeding system, denaturizing tumor cells detached during penetration of the biopsy needle or treatment electrode.